Dynamic contrast-enhanced micro-computed tomography correlates with 3-dimensional fluorescence ultramicroscopy in antiangiogenic therapy of breast cancer xenografts - Poeschinger, Thomas; Renner, Anja; Eisa, Fabian; Dobosz, Michael; Strobel, Steffen; Weber, Thomas G.; Brauweiler, Robert; Kalender, Willi Alfred; Scheuer, Werner (Investigative Radiology, 2014)
Dynamic contrast-enhanced (DCE) micro-computed tomography (micro-CT) has emerged as a valuable imaging tool to noninvasively obtain quantitative physiological biomarkers of drug effect in preclinical studies of antiangiogenic compounds. In this study, we explored the ability of DCE micro-CT to assess the antiangiogenic treatment response in breast cancer xenografts and correlated the results to the structural vessel response obtained from 3-dimensional (3D) fluorescence ultramicroscopy (UM).Two groups of tumor-bearing mice (KPL-4) underwent DCE micro-CT imaging using a fast preclinical dual-source micro-CT system (TomoScope Synergy Twin, CT Imaging GmbH, Erlangen, Germany). Mice were treated with either a monoclonal antibody against the vascular endothelial growth factor or an unspecific control antibody. Changes in vascular physiology were assessed measuring the mean value of the relative blood volume (rBV) and the permeability-surface area product (PS) in different tumor regions of interest (tumor center, tumor periphery, and total tumor tissue). Parametric maps of rBV were calculated of the tumor volume to assess the intratumoral vascular heterogeneity. Isotropic 3D UM vessel scans were performed from excised tumor tissue, and automated 3D segmentation algorithms were used to determine the microvessel density (MVD), relative vessel volume, and vessel diameters. In addition, the accumulation of coinjected fluorescence-labeled trastuzumab was quantified in the UM tissue scans to obtain an indirect measure of vessel permeability. Results of the DCE micro-CT were compared with corresponding results obtained by ex vivo UM. For validation, DCE micro-CT and UM parameters were compared with conventional histology and tumor volume.Examination of the parametric rBV maps revealed significantly different patterns of intratumoral blood supply between treated and control tumors. Whereas control tumors showed a characteristic vascular rim pattern with considerably elevated rBV values in the tumor periphery, treated tumors showed a widely homogeneous blood supply. Compared with UM, the physiological rBV maps showed excellent agreement with the spatial morphology of the intratumoral vascular architecture. Regional assessment of mean physiological values exhibited a significant decrease in rBV (P < 0.01) and PS (P < 0.05) in the tumor periphery after anti-vascular endothelial growth factor treatment. Structural validation with UM showed a significant reduction in reduction of relative vessel volume (rVV) (P < 0.01) and MVD (P < 0.01) in the corresponding tumor region. The reduction in rBV correlated well with the rVV (R = 0.73 for single values and R = 0.95 for mean values). Spatial maps of antibody penetration showed a significantly reduced antibody accumulation (P < 0.01) in the tumor tissue after treatment and agreed well with the physiological change of PS. Examination of vessel diameters revealed a size-dependent antiangiogenic treatment effect, which showed a significant reduction in MVD (P < 0.001) for vessels with diameters smaller than 25 ?m. No treatment effect was observed by tumor volume.Noninvasive DCE micro-CT provides valuable physiological information of antiangiogenic drug effect in the intact animal and correlates with ex vivo structural analysis of 3D UM. The combined use of DCE micro-CT with UM constitutes a complementary imaging toolset that can help to enhance our understanding of antiangiogenic drug mechanisms of action in preclinical drug research.
EVALuna2:10086